Evaluation of in vitro anti-acne activity of methanolic extracts of Cyperus rotundus and Nymphaea nouchali - Ranasinghe, Baladara H. T. S.; Weeraratne, Dinasha R.; Maddumage, Ridmi S.; Perera, Heeraluge F. H.; Fernando, Rathugamage S. P.; Silva, Athige R. N. (International Journal Of Community Medicine And Public Health, 2023)
Background: The objective of this study was to evaluate in vitro anti-acne activity against Staphylococcus aureus (S. aureus), Staphylococcus epidermidis (S. epidermidis), and Escherichia coli (E. coli) using the agar well diffusion method. Methods: Air-dried and ground, matured rhizomes of Cyperus rotundus (CR), petals and pollen of Nymphaea nouchali (NN) were macerated in methanol. The resultant extracts were concentrated using a rotary evaporator. The anti-bacterial activity was performed against Staphylococcus aureus (ATCC 25923), Staphylococcus epidermidis (ATCC12228), and Escherichia coli (ATCC 25922) using the agar well diffusion method, and gentamicin was used as a positive control. The whole experiment was done in triplicates. Results: The data obtained from dose-response curves, methanolic extracts of Cyperus rotundus rhizomes against staphylococcus aureus (IC50=819.2 µg/ml), Nymphaea nouchali pollens against Staphylococcus epidermidis (IC50=787.7 µg/ml) and combination against Escherichia coli (IC50=813.6 µg/ml) were exhibited the highest potency. A strong positive statistically significant correlation was exhibited between the zone of inhibition and the concentrations of all plant extracts. The p value was less than 0.05 (p<0.05) and all the R2 values were around 1. Conclusions: The maximum anti-bacterial potency against gentamicin equivalent was observed in S. aureus, S. epidermidis, and E. coli at the concentration of 15625 µg/ml in combination. The present study might bring progress in the treatment of acne using herbs and in developing herbal formulations for safe and effective management of the disease.